Hypertension and diabetes mellitus: a systematic review of the distribution, prevalence and its associated factors among police officers and security agents - Adagbasa, Ehimare; Atolagbe, James; Tajudeen, Waliu Adesegun (International Journal Of Community Medicine And Public Health, 2023)
Security agents and emergency responders are significant in ensuring the safety and security which lie at the heart of the prosperity of any nation, the relevance of exploring the prevalence of hypertension and diabetes mellitus among these populations, especially police officers increase progressively due to the growth. In this review, it had been described that there was a high prevalence of hypertension and diabetes mellitus among police officers and other emergency responders, and their associated factors were equally explored. A total of 23 most relevant articles was included, which followed the preferred reporting for systematic review and meta-analysis (PRISMA) guidelines. The general concepts and topics enclosed by PRISMA were all relevant to any systematic review, a fast systematic review of all articles published between 2013 and 2022 employing databases such as PubMed, Google scholar and other online databases was conducted. Included research covered studies involving hypertension, diabetes mellitus and its associated factors among emergency responders. 19,377 studies were collected and 23 articles satisfied the inclusion criteria, incusing cross-sectional studies, cohort studies and longitudinal, descriptive and quantitative observational studies. Studies show that prevalence was high for both variables and age, being a male, rest, body mass index (BMI), smoking and alcohol consumption were the significant associated factors among these working groups. Regular health screening and encouragement of healthy lifestyles are recommended.